Babalu Dance and Holistic Development of Early Childhood: A Case Study on the Integration of Traditional Arts in Early Childhood Education - Fatma Hadianti, Galuh; Sulis Setyaningrum, Ikha (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Traditional dance not only represents cultural heritage but also embodies pedagogical values that can be integrated into early childhood education. One such traditional dance that remains vibrant and practiced in the northern coastal region of Java is the Babalu Folk Dance, characterized by rhythmic, simple yet expressive movements. Although children’s dance practices have flourished in informal educational settings, the utilization of traditional dance as a child development–oriented learning medium remains severely limited. This study originates from this gap, noting the lack of systematic exploration of the contribution of traditional dance movement variations to the holistic development of early childhood. This research aims to analyze the movement structure of Babalu Dance and evaluate its potential in supporting five key developmental domains of early childhood: gross motor, fine motor, cognitive, socio-emotional, and artistic appreciation. Employing a qualitative case study approach, this study was conducted at Sanggar Putra Budaya Batang, involving six children aged 4–6 years, six dance instructors, and six parents. Data collection techniques included participatory observation, semi-structured interviews, and visual documentation, followed by thematic analysis. The findings reveal that each movement category—head, hand, foot, and body—specifically contributes to various dimensions of child development. Body and foot movements support balance and coordination; hand movements strengthen fine motor skills; and the choreographic structure fosters cognitive, social, and expressive aspects. This study underscores the potential of Babalu Folk Dance as a culturally grounded contextual learning medium and recommends its integration into character- and traditional arts–based early childhood education curricula.